Utilization of human papillomavirus testing for cervical cancer prevention in a university hospital - Rosekeila Simões Nomelini; Ana Cristina Macêdo Barcelos; Márcia Antoniazi Michelin; Sheila Jorge Adad; Eddie Fernando Candido Murta (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2007)
This study aimed to evaluate the performance and cost of using polymerase chain reaction (PCR) and hybrid capture in the detection of cervical intraepithelial neoplasia (CIN) in patients with cytological abnormalities (ASCUS/low-grade squamous intraepithelial lesion - LSIL), and the feasibility of implementing these methods in Brazil's Unified National Health System (SUS). Colposcopy gave a negative predictive value of 92.86% and efficiency of 87.8% for diagnosing CIN. The sensitivity of PCR and hybrid capture for detecting CIN was 83.33% and 66.67%, respectively, and the negative predictive value for diagnosing CIN2/CIN3 was 100% and 94.74%, respectively. The annual cost for 80 patients was lower when all patients with ASCUS/LSIL were referred for colposcopy than when HPV testing was performed and those with positive results were referred for colposcopy. Therefore, at present, it is financially unfeasible for the National Health System to implement HPV testing to screen patients with cytological abnormalities (ASCUS/LSIL). However, considering that large-scale use might make such methods cheaper, PCR should be the chosen method, since it is less expensive, more sensitive, and has a high negative predictive value.